The new development trend of operational research in civil engineering and sustainable development as a result of collaboration between german‐Lithuanian‐Polish scientific triangle - Jolanta Tamošaitienė; Lina Bartkienė; Tatjana Vilutienė (Journal of Business Economics and Management, 2010)
In this article the scientific cooperation between the three academic centres from Germany, Lithuania and Poland, represented by Prof. F. Peldschus (Leipzig University of Applied Sciences), Prof. E. K. Zavadskas (Vilnius Gediminas Technical University), and Prof. O. Kapliński (Poznan University of Technology), is presented. Formal meetings have been called Colloquia, and were organized every two years in different academic centres.